Implementasi Pembuatan Teknologi Tepat Guna Budikdamber AutoFeeder (Pakan Otomatis) Dalam Pengembangan UMKM Budidaya Lele Di Kelurahan Tanjungsari Kota Blitar - Gideon Setyo Budi Witjaksono; Sihab Kurnia Hakim; Ihza Muhammad Ersyaf; Wildan Jovian Wahyu Tyas Saputra; Wahyu Nur Rafita; Ayu Cahyasusanti (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Cultivating catfish is an activity that can be made a profession by some people. As was done by the East Java "Veteran" UPN KKN-T students, they analyzed catfish farming through the method of distributing questionnaires tocatfish farming business actors in Tanjungsari Village. Theytry to provide things that are more efficient in the context of catfish farming, students from the UPN try to share the knowledge they gain at the university to the village community where they do their service. One of the things that has been done to provide time efficiency for catfish cultivators is to provide an innovation called Budikdamber Autofedeer where this technology can be very helpful in terms of catfish farming. The results of the application of technology by UPN "Veteran" East Java KKN-T students can increase the income of people who are engaged in catfish farming because this technology can produce not only one crop but two yields in two different ways.